Prototype of Long-Range Radio Communication for e-Nelayan Devices using LoRaWAN - Febri Dawani; Syifaul Fuada; Sinantya Feranti Anindya; Aditia Rifai; Erick Adinugraha; Irfan Gani Purwanda; Trio Adiono (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2018)
In this paper, development progress of a long-range radio communication-based fishing assistant system called e-Nelayan is reported. The purpose of the system is to increase the productivity, safety, and welfare of fishermen using mobile phone and long-range radio based system that enables them to report maritime violations, access and exchange information regarding weather, fishing area, marketplace, and also communication with mainland using Android-based mobile phone within extended range. We used LoRaWAN as a base technology for long-range communication scheme. In this work, the test conducted to obtain an insight to e-Nelayan device (LoRa-based) received RSSI and its packet loss. The received data collected in a server also includes the GPS tracking data. The test results show that our system reached approximately 5 km of distance between end-node to the LoRa Gateway within urban area (LoS configuration) and about 2 km for NLOS configuration.